OLDER AGE AND PARKINSON’S DISEASE - Petrović, Igor; Tomić, Aleksandra; Dragašević Mišković, Nataša; Ječmenica Lukić, Milica; Marković, Vladana; Kresojević, Nikola; Stanković Tutuš, Iva; Svetel, Marina; Kostić, Vladimir (Medicinski podmladak, 2024)
The etiology of PD remains unclear, with aging identified as the primary risk factor. Epidemiological data show an increasing prevalence of PD with age, affecting 1-2% of persons over 65. The incidence of PD rises rapidly with age, peaking in the eighth decade of life. Motor symptoms in older PD patients are characterized by severe hypokinetic syndrome, axial features, and postural and gait difficulties. Non-motor symptoms, including cognitive impairment, sleep disorders, and dysautonomia, significantly impact quality of life. The prevalence of dementia and frailty increases with age and PD duration.  This age group faces a higher risk of side effects from antiparkinsonian therapies, thus therapeutic adjustments are necessary to address the progression of both motor and non-motor symptoms.The differential diagnosis of PD involves distinguishing it from other parkinsonian syndromes, which can be challenging due to overlapping symptoms and the absence of specific diagnostic tools.The presence of mild parkinsonian signs in aged population predicts worse outcomes, including dementia, disability, and mortality. This review provides a comprehensive overview of the clinical manifestations, therapeutic considerations, and differential diagnosis of PD in older adults, highlighting the importance of individualized treatment approaches.
Keywords: Parkinson’s disease; aging; motor and non-motor symptoms